Overview on Nanogrid: Concept, Opportunities, Challenges, and Future Prospects-An Analysis - Turan, Onur; Durusu, Ali; Yumurtaci, Recep (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
Conventional electricity generation, heavily dependent on centralized fossil fuel and nuclear power plants, continues to drive greenhouse gas emissions and environmental degradation. Nanogrids (NGs) offer a promising decentralized alternative by integrating renewable energy sources (RES) with localized control, yet their techno-economic feasibility under diverse climatic conditions in developing regions remains insufficiently quantified. Previous studies have primarily emphasized architectures, converter technologies, or general reviews, but have not provided climate-sensitive, quantified techno-economic assessments of residential NGs in Mediterranean and developing country contexts, leaving a critical research gap. This study addresses that gap through a comprehensive HOMER Grid based analysis of rooftop solar NG systems across four Turkish cities within different geographical regions of T & uuml;rkiye. Levelized cost of energy (LCOE), net present cost (NPC), renewable fraction, and CO2 reduction are used to evaluate system viability under T & uuml;rkiye specific tariffs and load profiles. The results demonstrate that optimized NG configurations achieve more than 70% lower LCOE than only grid base, with Izmir showing the most favourable outcomes in terms of renewable penetration, LCOE and emissions reduction. From a practical perspective, the study also identifies deployment barriers including high battery capital costs, rooftop space constraints, and regulatory instability. Limitations of the analysis include the assumption of nominal temperature conditions in the BESS model and the restricted scope of tariff sensitivity, which should be refined in future research. Overall, the findings confirm that NGs are both economically viable and environmentally beneficial when supported by stable policies, while also providing actionable insights for sustainable energy transitions in T & uuml;rkiye and comparable regions.
Keywords: Costs; Levelized cost of energy; Reviews; Electricity; Tariffs; Renewable Portfolio Standard; Net zero; Batteries; Urban areas; Resilience; Nanogrid; renewable energy; prosumers; distributed generation; DC-DC CONVERTER; ENERGY-STORAGE SYSTEMS; RURAL ELECTRIFICATION; POWER MANAGEMENT; DISTRIBUTION NETWORKS; SUPERVISORY CONTROL; TRANSMISSION LOSS; DC/DC CONVERTER; AC/DC CONVERTER; PV; Computer Science; Engineering; Telecommunications